PERBEDAAN KUALITAS TANAMAN JAGUNG BERCIRI BROWN MIDRIB RESISTANCE DARI DATARAN RENDAH DAN TINGGI DI WILAYAH YOGYAKARTA - B. Suwignyo; B. Suhartanto; Dj. Soetrisno (Universitas Tribhuwana Tunggadewi, 2012)
This study aimed to determine the difference quality of corn plants with brown midrib resistance characterized on low and high land of Yogyakarta Province. Development of farm world will always be followed by efforts to satisfy meet quality and sustainable food supply. Problems of tropical forage feed provision are not only the quantity but also quality and continuity. Lignifications is one of the limitation factor for forage that will affect to low digestibility level. Indonesia as a country that is located in the tropics actually have the potential of corn forage. There is a type of corn with brown color on the underside of leaves around the middle of the bone known as the brown midrib resistance (BMR) is the hallmark of corn plants that have low lignin content. BMR corn with these characteristics is genetic heredity. Nutritional quality analysis for corn plant have done at the Laboratory of Food Forage and Pastures Livestock Husbandry Faculty of the University of Gadjah Mada. Corn plant derived from the lowlands have the potential dry matter better in addition to trend lower lignin than corn from the highlands